662Factors associated with smoking continuation and indoor smoking among pregnant women's partners. (2nd September 2021) - Murakami, Keiko; Obara, Taku; Ishikuro, Mami; Ueno, Fumihiko; Noda, Aoi; Kuriyama, Shinichi
Abstract: Background: Secondhand smoke by partners is a major source of exposure for non-smoking women. However, factors associated with smoking continuation and indoor smoking among pregnant women's partners remain unknown. Methods: We used data from 6348 partners of non-smoking pregnant women who participated in the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study in Japan from 2013 to 2017. Partners' age, educational attainment, equivalent household income, and pregnant women's smoking history (never, quitting before pregnancy awareness, quitting after pregnancy awareness) were used as explanatory variables. Multivariate logistic regression analyses were conducted to examine the associations between these variables and smoking continuation/indoor smoking of partners. Results: Among 6348 partners, 2506 partners had been smokers at pregnancy awareness. Among them, the prevalence of smoking continuation after pregnancy awareness was 92.0%. Partners whose wives had quitted smoking after pregnancy awareness were less likely to continue smoking than partners whose wives had never smoked; the odds ratio was 0.57 (95% confidence interval, 0.41–0.80). Among partners who continued smoking, the prevalence of indoor smoking was 30.7%. Partners with ≤high school education were more likely to smoke indoors than partners with ≥university education; the odds ratio was 1.60 (95% confidence interval, 1.23–2.07). Conclusions: Women's smoking cessation after pregnancy awareness was associated with decreased risk of partners' smoking continuation, and lower level of partners' education was associated with increased risk of partners' indoor smoking. Key messages: Interventions for both women and their partners may be effective in reducing secondhand smoke exposure during pregnancy.